EFEKTIVITAS PLATFORM LEARNING MANAGEMENT SYSTEM BERBASIS WEB SEBAGAI MEDIA PEMBELAJARAN BLENDED LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Falih Ihza; Umali Hayati; Popi Dayurni; Dewi Surani (Program Studi Teknologi Informasi, Universitas Muhammadiyah Muara Bungo, 2023)
The study aims to determine how much the effectiveness of the Learning Management System Platform as a Blended Learning Media on Student Learning Motivation. This type of quantitative research is pre-experimental, the research design used is one group pretest postest. This research was conducted at SMKN 1 Kota Serang, with a population of X TKJ class totaling 78 people where the researchers previously conducted instrument trials, the researchers then conducted research through questionnaires., the sample in the study of X TKJ 1 class students as many as 38 people and data analysis was carried out by descriptive analysis test, hypothesis testing and n-gain test. Based on the results of the study, it was found that the data was normal and the results of the learning motivation questionnaire were 70.18% for the pretest and 90.26% for the posttest, while the results of the hypothesis test with the results of the Sig. value obtained was 0.000 <0.05 which means that the H0 hypothesis is rejected and the Ha hypothesis is accepted, supported by the n-gain test obtained of 0.67 (medium) for learning motivation. Based on the results of the pretest and posttest, hypothesis testing and n-gain test, it is concluded that the use of the Diriku Learning Management System platform as a Blended Learning-based learning media is effective on student learning motivation with moderate criteria.